SAT0454 Relationship Between Trabecular Bone Score and Bone Mineral Density in Systemic Sclerosis. (9th June 2015) - Botticella, G.; Paolino, S.; Casabella, A.; Fasciolo, D.; Seriolo, B.; Cutolo, M.
Abstract : Background: Patients affected by Systemic Sclerosis (SSc) present an increased risk of osteoporosis or osteopenia and fractures as a result of many factors including chronic inflammatory state, malabsorption, low vitamin D levels, physical inactivity (1). The Trabecular Bone Score (TBS) is a index extracted from the dual-energy X-ray absorptiometry (DXA) that provides an indirect measurement of bone axial microarchitecture and allows to get informations about bone quality (2). Objectives: The aim of this study is to investigate bone quality using TBS in SSc patients according to their different nailfold videocapillaroscopic (NVC) patterns of microangiopathy ("Early", "Active", "Late") in order to evaluate the possible association between BMD and TBS. Methods: 74 female postmenopausal patients (mean age 65±9 years) affected by SSc ("early" n=16, "active" n=12 and "late" n=46, NVC pattern) and 60 age-matched healthy controls (mean age 64±11 years) were studied. BMD (g/cm 2 ) of the lumbar spine (L1-L4) was analyzed using DXA scan (Lunar Prodigy). Lumbar spine TBS was derived for each spine DXA examination blinded to clinical parameters and outcomes using TBS iNsight Medimaps (Lunar Prodigy). TBS value >1.350 is considered normal whereas TBS value <1.200 indicates a degraded bone microarchitecture (2) NVC patterns were analyzed according to the previous reported methods (3) Results: BMD was found significantly lower in SSc patients than in matched control group (respectively, Lumbar spine: 0.984±0.191 g/cm 2 vs 1.240±0.932 g/cm 2 ; Femoral neck: 0.764±0.212 g/cm 2 vs 0.845±0.164 g/cm 2 ; Ward 0.583±0.173 g/cm 2 vs 0.657±0.106 g/cm 2 ; Trocanther: 0.666±0.104 g/cm 2 vs 0.725±0.143 g/cm 2 ; Total hip: 0.827±0.182 g/cm 2 vs 1.033±0.161 g/cm 2, all p<0.001). Lumbar spine TBS was found significantly lower in SSc patients than in matched control group (respectively, 1.092±0.163 vs 1.261±0.126, p<0.001). Interestingly, a positive correlation was found between BMD and TBS (Lumbar spine: r=0.4, p<0.01; Femoral neck: r=0.3, p<0.01; Ward: r=0.4, p<0.05; Trocanther: r=0.4 p<0.01; Total hip: r=0.3, p<0.01) in SSc patients. In particular, decreased BMD and TBS were found in "late" SSc patients vs "early"/"active" patients (Lumbar spine 0.892±0.142 g/cm 2 vs 1.122±0.205 g/cm 2 ; Femoral neck: 0.647±0.241 g/cm 2 vs 0.775±0.243 g/cm 2 ; Ward 0.596±0.141 g/cm 2 vs 0.673±0.138 g/cm 2 ; Trocanther: 0.641±0.115 g/cm 2 vs 0.763±0.135 g/cm 2 ; Total hip: 0.696±0.160 g/cm 2 vs 0.791±0.164 g/cm 2 ; TBS 1.121±0.121 VS 1.29±0.103 all p<0.01) Conclusions: This detailed study shows a decreased BMD and TBS value in SSc patients when compared to healthy controls. In addition TBS, evaluated at the lumbar spine, with lumbar and femoral BMD, could discriminate patients with alterated bone microstructure and could become a new clinical tool in the general diagnosis of osteoporosis. In particular, the association with the "late" NVC scleroderma pattern of microvascular damage, may suggest that low vascular perfusion related to microangiopathy probably might further influence bone mass and quality of skeleton. References: Cutolo M et al. Autoimmun Rev 2011;12:84-87. Roux JP et al. Osteoporosis Int 2013; 24(9):2455-60. Cutolo M et al. J Rheumatol 2000; 27 (1):155-60 Disclosure of Interest: None declared